Colorectal cancer biomarkers and their impact on the clinical practice - Crespo, James; Victorino, Ana Paula; Araujo, Kelly; Araujo, Luiz Henrique; Vieira, Fernando Meton de Alencar Camara (Brazilian Journal of Oncology, 2021)
Colorectal cancer (CRC) holds third place in the global ranking of malignancies worldwide. Patients with CRC commonly show distinct outcomes and treatment responses due to their biological features and tumoral biomarkers. This review explores the repertoire of molecular biomarkers in CRC, comprised of chromosomal aberrations and genomic instability and genetic mutations. We also underline the stratification of CRC patients into four clinically defined subsets: CMS1 (MSI, immune); CMS2 (canonical); CMS3 (metabolic); and CMS4 (mesenchymal), as well as novel techniques to be applied very soon in the field, such as cell-free DNA, tumor mutational burden, and microbiome profiling.
Keywords: Biomarcadores; Genômica; Prognóstico; Agentes antineoplásicos; Neoplasias colorretais.